Brucellosis in patients with pyrexia of unknown origin in Assam, India: a retrospective record review - Takujungla Jamir, MAE; Sahabuddin Ahmed Laskar, BVScAH; Vaishali Sarma, MD; Nripendra Nath Deka, MBBS (Elsevier, 2020)
Background: Globally, around 500 000 human brucellosis cases are reported every year. In India, the burden of human brucellosis is likely underestimated because of limited laboratory capacity. In this study, we aimed to estimate brucellosis burden in patients with pyrexia of unknown origin (PUO) attending Amsing Jorabat Sub-centre in Kamrup Metro, Assam, India-an area with 10% prevalence of animal brucellosis. Methods: We retrospectively reviewed records of PUO patients attending Amsing Jorabat Sub-centre between Jan 1 and Oct 31, 2014. We defined a case as Brucella-positive if a Rose Bengal plate test or serum agglutination test, or both, were positive along with IgM or IgG positivity. We reviewed records of routine animal surveillance by Assam Agriculture University to see if cases had Brucella-positive animals in their farms. We used EpiInfo 7.1 to analyse data. Findings: Of the 46 PUO patients included in the study, 25 (54%) were Brucella-positive. Median age of brucellosis patients was 33 years (range 18-67 years). Among the 25 cases, 88% were men and 80% were dairy farmers. All 25 case-patients owned dairy farms or worked as farm attendants. Most common presenting symptoms were arthralgia (n=17 [68%]), fever (12 [48%]), and night sweats (12 [48%]). Patients became ill mostly during March (7 [28%]) and July (6 [24%]). Most Brucella-positive patients (17 [68%]) were from Shillongia village. All case-patients were engaged in milking and more than half (19 [76%]) had handled abortus during birthing on the farm. Interpretation: More than half of PUO cases were brucellosis cases in dairy farm workers who had brucellosis-positive animals on their farms. We recommend multisector coordination involving health and veterinary departments to improve surveillance and control of brucellosis. Funding: None.